Modernization of Pesantren Education in the Reform of Indonesia's Islamic Education System: A Systematic Literature Review - Rita Sriayu; Siti Kamilah; Muchammad Eka Mahmud; Muljono Damopolii; Fitrah Elnurianda (Al-Qalam Institute, 2025)
As the oldest Islamic educational institutions in Indonesia, pesantren face transformative pressures from globalization, digitalization, and national education reform, yet existing scholarship on their modernization remains fragmented across separate dimensions. This study aims to identify the concept and typology of pesantren modernization, to analyze the forms of transformation within the pesantren education system, and to describe the implications of that modernization for the development of Islamic education in Indonesia. It employs a Systematic Literature Review guided by the PRISMA 2020 framework, searching six databases, namely Google Scholar, SINTA, Scopus, ScienceDirect, ERIC, and DOAJ, from which 24 of 263 identified articles met the inclusion criteria. The synthesis reveals that modernization proceeds across four interdependent dimensions, namely integrative curriculum, active-participatory learning methods, professional institutional management, and digital technology adoption, and that pesantren respond through three typologies: progressive adaptive, selective adaptive, and resistive. These findings imply improved graduate competencies, a strengthened social function, and the emergence of a hybrid model that holds tradition and modernity together. The study recommends a transformative-integrative model of pesantren education responsive to twenty-first-century needs.